URBANIZATION AND HEALTH EDUCATION IN MODERN JAPAN /In the case of vegetable production among suburban dwellers in Ulaanbaatar/ - L.Surenbaatar; B.Khishigdelger, (Journal of Business and Innovation (Бизнес & Инноваци), 2023)
Since the end of World War II, the Japanese society experienced a rapid modernization. However the modernization deeply affected the family structure and kinship ties, and thus gave positive as well as negative impact on its health environment. In this paper, we will show how family change caused by modernization brought unwillingly negative influence on health conditions. In Western countries, the family garden has been considered as a means of improving marginalized people’s nutritional status and their quality of life at the same time, by encouraging mutual assistance within the neighborhood. Under this perspective, a team from our research tried to promote vegetable gardens among residents of a Ger district in Ulaanbaatar from 2016 to 2019. In this communication, we discuss the manner in which the residents adopted vegetable gardens, and we specify the reasons for this adoption.